GAMBARAN PENGETAHUAN ORANGTUA TERHADAP PENANGANAN KEJANG DEMAM PADA ANAK DI RUMAH SAKIT SANTA ELISABETH BATAM KOTA TAHUN 2022 - Ance M. Siallagan; Lindawati Simorangkir; Nadia Oktavia Pasaribu (Jurnal Cakrawala Ilmiah, 2024)
This febrile seizure attack is difficult to identify when it appears. So parents or caregivers of children, especially their mothers, need to be given knowledge about febrile seizures and initial actions for managing febrile seizures at home in children who have febrile seizures. The purpose of this study was to describe the knowledge of parents on the handling of febrile seizures in children at Santa Elisabeth Hospital Batam City in 2022. The research design was a cross sectional design method. The sampling technique is total sampling with a total sample of 64 people. The measuring instrument used is a questionnaire. The results showed that most had a good level of knowledge (51.6%). So it can be concluded that parents already have good knowledge which is influenced by age, gender and level of education of parents.